Annual Plant Reviews Online 2021
DOI: 10.1002/9781119312994.apr0774
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years ofGynandropsis gynandraResearch for Improvement of Nutrient‐Rich Leaf Consumption: Lessons Learnt and Way Forwards

Abstract: Article 25fa states that the author of a short scientific work funded either wholly or partially by Dutch public funds is entitled to make that work publicly available for no consideration following a reasonable period of time after the work was first published, provided that clear reference is made to the source of the first publication of the work.This publication is distributed under The Association of Universities in the Netherlands (VSNU) 'Article 25fa implementation' project. In this project research out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…Gynandropsis gynandra is an essentially cosmopolitan species found across Africa, Asia, the Middle East and Australasia, and has been introduced to the Caribbean, Southern and Northern America and Central and Northern Europe (Chweya and Mnzava, 1997). Despite the wide distribution range of the species, G. gynandra is considered an “orphan” or “neglected” species becaus e of the lack of research efforts to develop genetic and genomic resources (Achigan-Dako et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gynandropsis gynandra is an essentially cosmopolitan species found across Africa, Asia, the Middle East and Australasia, and has been introduced to the Caribbean, Southern and Northern America and Central and Northern Europe (Chweya and Mnzava, 1997). Despite the wide distribution range of the species, G. gynandra is considered an “orphan” or “neglected” species becaus e of the lack of research efforts to develop genetic and genomic resources (Achigan-Dako et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, owing to its potential to address hunger, malnutrition, and stunting of the African population, the species has been included in the list of 101 crops by the African Orphan Crops Consortium (AOCC) (Hendre et al, 2019; Jamnadass et al, 2020). The genome sequence of the species would therefore represent an important resource for breeding programs targeting traits ranging from higher leaf yield to increased secondary metabolite production and disease resistance (Achigan-Dako et al, 2021). Second, G. gynandra is a C4 plant and the Cleomaceae family contains both C3 and C4 plants, as well as C3-C4 intermediates (Marshall et al, 2007; Feodorova et al, 2010; Koteyeva et al, 2011; Bayat et al, 2018; Parma et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors can affect leaf nutritional values, including soils, agronomic practices (fertilization, harvest time), developmental stages, cooking methods, and postharvest techniques. As nutritional value is genotype-specific, more investigations are needed to assess the effects of these factors on the nutritional values of the species (Moyo et al, 2018;Sogbohossou et al, 2019;Achigan-Dako et al, 2021). Other key components include the bioavailability of nutrients and the effects of the different cooking processes on bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, vigorous promotion of its conservation and intensive use needs to be addressed (Coq-Huelva et al, 2017). Several reports showed that germplasm resources for C. gynandra are available in local, regional, and international genebanks (Achigan- Dako et al, 2021). Currently, there are about 295 accessions of these species available at World Vegetable Centre (http://www.seed.wordveg.org/) collected from Southern African, Eastern Africa and Asia (Moyo and Aremu, 2022).…”
Section: Potential Of Breeding C Gynandramentioning
confidence: 99%
“…For example, there are 45 accessions of C. gynandra comprising 28 landraces, 9 wild, 7 weedy and 1 unknown accessions at the National Gene Bank of Kenya (Kemei et al, 1995). According to Achigan-Dako et al (2021), 164 accessions of C. gynandra germplasm were recently collected from Benin, Burkina Faso, Ghana, Niger and Togo and were maintained at the University of Abomey-Calavi's Laboratory of Genetics, Biotechnology, and Seed Sciences in Benin. More than a decade ago, it was reported that about 184 accessions of C. gynandra were collected in South Africa and Tanzania by National Gene Bank of South Africa and National Plant Genetic Resource Center (Arusha-Tanzania) (Van Rensburg et al, 2007a).…”
Section: Potential Of Breeding C Gynandramentioning
confidence: 99%